Oral Potentially Malignant Disorders (OPMD): What is the clinical utility of dysplasia grade?. (4th March 2021) - Pritzker, Kenneth P. H.; Darling, Mark R.; Hwang, Jason T-K; Mock, David
ABSTRACT: Introduction: Oral epithelial dysplasia is considered a potential histologic precursor of subsequent squamous cell cancer. As standard clinical practice, pathologists grade dysplasia to assess risk for progression to malignancy. Except for the most advanced grade, severe dysplasia, dysplasia grading has failed to correlate well with the risk to develop invasive cancer. The questions of what process dysplasia grading best represents and what clinical utility dysplasia grading may have are explored. Areas covered: This narrative review is based on PubMed search with emphasis on papers since 2010. Epithelial dysplasia as a precursor lesion of cancer and dysplasia grading as a risk assessment tool for progression to cancer are discussed. The close clinical association of dysplasia with known carcinogens, alcohol, and tobacco products is presented. Expert opinion: Oral epithelial dysplasia is often, associated with prolonged exposure to tobacco and alcohol products. With reduction of carcinogen exposure, dysplasia is known to regress in some cases. It is proposed that histologic dysplasia grade together with macroscopic images of dysplastic clinical lesions be used as an educational tool to incentivize patients to reduce their known carcinogen exposure. This strategy has the potential to reduce lesion progression thereby reducing the disease burden of oral cancer.